History and prospects of psychosurgical interventions in the treatment of mental disorders. The arguments «pro et contra» - M. V. Ivanov; V. V. Stanovaya; T. A. Skoromets; V. A. Mikhailov; M. A. Akimenko (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Most patients with mental disorders can be effectively treated with therapies such as pharmacological therapy, psychotherapy, electroconvulsive therapy. These treatments can be used individually or in combination. However, some patients either do not respond to therapy or experience severe side effects. It is for these patients that neurosurgical procedures may be considered. Psychosurgery is considered brain surgery used to alleviate painful mental manifestations or to mitigate the course of mental illness. Psychosurgery can be talked about as a way to correct mental disorders. It should be considered as a link in the system of treatment and rehabilitation of patients with therapeutically resistant mental disorders.Despite the centuries-old history of psychosurgery, the question of the expediency of using surgical methods for the treatment of mental disorders still remains one of the intractable ones. Today, psychosurgery is a low-traumatic operation, which is associated with targeted and dosed interventions on the deep parts of the human brain. This review describes the main stages in the development of psychosurgery, the main surgical methods used to treat mental disorders, and also discusses the future probable directions of neurosurgical treatment in a psychiatric clinic. The argumentation for the use of this type of treatment in the formation of manifestations of therapeutic resistance is given. Taking into account the diametrality in assessing the feasibility of using the methods of psychosurgery, the concluding part of the article discusses the pros and cons of surgical treatment of mental disorders.